Perception of Student Readiness in Mastering Core Skills of the Malaysian Skills Certificate / Persepsi Kesediaan Penguasaan Pelajar Dalam Kemahiran Teras Sijil Kemahiran Malaysia (Sains Humanika, 2024)
The Malaysian Skills Certification (SKM) is implemented as a formal certificate of recognition for individuals who demonstrate the ability acquired or practiced efficiently to perform a task. Among the aspects emphasized in Malaysian skills certification are core abilities. Therefore, this study aims to look at the perception of students' mastery readiness of core abilities among students of the Faculty of Technical and Vocational Education (FPTV), Universiti Tun Hussein Onn Malaysia. This study uses a quantitative approach with a survey research design. Using a questionnaire instrument based on SKM level 3 core skills assessment module which consists of six elements namely effective communication, information technology awareness, leadership skills, workplace ethics, administrative skills and health, safety and environmental implementation awareness. The study sample consisted of 92 final year students from General Machining, Building Construction, Catering, Welding & Metal Fabrication, Electrical & Electronics, Creative Multimedia and Refrigeration & Air Conditioning courses. The study's results underwent analysis via the Statistical Package for Social Science (SPSS) software. This analysis encompassed both descriptive techniques, such as percentages, means, and standard deviations, as well as inferential methods, including T-tests and ANOVA. The study's findings indicate that FPTV students' perception of their readiness to master the core abilities required for Malaysian skills certification is notably high. Therefore, students who will take the SKM verification will be at a high level of mastery readiness. These skills are essential to create a highly skilled workforce that has mastered technical skills as well as core skills.
Keywords: Core Abilities, effective communication, ICT awareness, leadership skills, workplace ethics, administrator skills and health and environmental awareness